COVID-19 medidas preventivas: Lávese las manos frecuentemente - Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman; Michelle Danyluk (EDIS)
These flyers, written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman (NC State University Extension), provide quick, digestible information regarding prevention of COVID-19 and procedures for food service, grocery stores, and other food-related businesses. This flyer in particular is the Spanish translation of FSHN20-11/FS334: COVID-19 Preventative Measures: Clean Your Hands Often. Published by the UF/IFAS Food Science and Human Nutrition Department, March 2020.